Pengenaan Pajak Penghasilan terhadap Pengusaha dalam Transaksi Perdagangan Online (E-commerce) Studi Pengusaha Online di Yogyakarta - Tahar, Afrizal; Septiani, Delvina Dwi (E-Jurnal Akuntansi, 2021)
This research was conducted to examine the imposition of income tax on entrepreneurs in online trading transactions. This study aimed to know online entrepreneurs’ perceptions regarding the implementation of e-commerce income tax. This study employed semi-structured interview techniques to obtain the necessary information in data collection. The informants in the study were selected by purposive sampling, and they came from KPP Pratama Yogyakarta, Tax Consultants in Yogyakarta, Tax Experts in Yogyakarta, Information Technology Experts in Yogyakarta, and Online Business Entrepreneurs domiciled in Yogyakarta. This study’s findings revealed that the income of online business entrepreneurs is the tax’s object, and the collection is the same as other tax collections. Online entrepreneurs agreed to be taxed but only within specific transaction limits. Keywords: Income Tax; Taxpayer’s Awareness; E-Commerce.